2012
DOI: 10.1128/mcb.00724-12
|View full text |Cite
|
Sign up to set email alerts
|

Upstream Stimulatory Factor 2 and Hypoxia-Inducible Factor 2α (HIF2α) Cooperatively Activate HIF2 Target Genes during Hypoxia

Abstract: While the functions of hypoxia-inducible factor 1␣ (HIF1␣)/aryl hydrocarbon receptor nuclear translocator (ARNT) and HIF2␣/ARNT (HIF2) proteins in activating hypoxia-inducible genes are well established, the role of other transcription factors in the hypoxic transcriptional response is less clear. We report here for the first time that the basic helix-loop-helix-leucine-zip transcription factor upstream stimulatory factor 2 (USF2) is required for the hypoxic transcriptional response, specifically, for hypoxic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
94
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(108 citation statements)
references
References 111 publications
10
94
1
2
Order By: Relevance
“…Such a multifactorial transcription complex has been termed the 'enhanceosome' (Thanos and Maniatis, 1995). USF2 has been identified as a HIF-2-specific co-transcriptional factor that not only is required for HIF-2 target gene activation but also is required for HIF-2-dependent tumorigenicity in vitro in several cell lines including mouse embryonic stem cells and Hep3B cells (Pawlus et al, 2012). It has additionally been shown that USF2 binds to HIF-2 target genes in vivo and contributes significantly to hypoxiamediated increase in CBP and p300 binding to the HIF-2 target genes PAI-1 and EPO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a multifactorial transcription complex has been termed the 'enhanceosome' (Thanos and Maniatis, 1995). USF2 has been identified as a HIF-2-specific co-transcriptional factor that not only is required for HIF-2 target gene activation but also is required for HIF-2-dependent tumorigenicity in vitro in several cell lines including mouse embryonic stem cells and Hep3B cells (Pawlus et al, 2012). It has additionally been shown that USF2 binds to HIF-2 target genes in vivo and contributes significantly to hypoxiamediated increase in CBP and p300 binding to the HIF-2 target genes PAI-1 and EPO.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, comparison at the same time point of 15 min suggests that, as expected, HIF-2α is more stable during hypoxia (without new protein synthesis) than during normoxia (despite ongoing protein translation). We then tested the effect of D4476 on the interaction of HIF-2 with the upstream stimulatory factor 2 (USF2), as it has been reported that this is necessary for optimal gene expression of EPO and PAI-1 (Pawlus et al, 2012). Huh7 cells overexpressing Flagtagged USF2 and incubated under hypoxia in the presence or absence of D4476 were subjected to immunoprecipitation with an anti-Flag antibody.…”
Section: Ck1δ Does Not Affect Protein Stability Of Hif-2α or Its Intementioning
confidence: 99%
“…This amino acid motif matches the consensus sequence for the basophilic AGC kinases (such as protein kinase B), which regulate cell migration and whose activity is stimulated by integrin binding and interaction with T-cell receptors (21). C5orf30 sequences also contains a motif matching closely the consensus for CDK1 phosphorylation (amino acids [20][21][22][23][24][25][26][27][28][29][30], which coupled to recognition sequences for cyclins (amino acids 139-170) is a strong indication of a roles for C5orf30 in the cell cycle. C5orf30 encodes a basic polypeptide (pI 9.5), a feature typical of proteins interacting with phospholipids, membranes, and/or nucleic acid interactions.…”
mentioning
confidence: 99%
“…Ultimately, we mined the RegulomeDB database to identify regulatory elements in noncoding regions of the human C5orf30 potentially affected by the RA-associated rs26232 SNP in the first intron of this gene (18). The ENCODE analysis indicate that this SNP is likely to affect the binding site for several transcription factors, of particular interest, USF2, required for the hypoxic transcriptional response and the activation of HIF genes (22), and BHLHE40, a regulator of chondrogenesis.…”
mentioning
confidence: 99%
“…Many of the hypoxia adaptations are mediated by the activation of specific genes through hypoxia-inducible factors (HIFs). HIFs, transcription factors associated with the cellular response to hypoxia (Pawlus et al, 2012), upregulate the expression of several hypoxia response genes, including glycolytic enzymes, vascular endothelial growth factor, matrix metalloproteinase (MMP)-9, transforming growth factors α and β, and numerous others (Shi et al, 2007;Fu et al, 2012). Collectively, these factors modulate cancer cell metabolism and can promote angiogenesis, invasion, and metastasis, leading to a poor outcome, suggesting that HIF proteins may represent suitable targets for antitumor therapies (Kaya et al, 2012;Hartwich et al, 2013;Saponaro et al, 2013).…”
Section: Introductionmentioning
confidence: 99%